Devil's brood - Penman, Sharon Kay (G. P. Putnam's Sons, 2008)
Where the second novel in the trilogy, Time And Chance, dealt with the extraordinary politics of the twelfth century, climaxing with the murder of Thomas Becket and Henry's confrontation with the Church and self-imposed exile to Ireland, Devil's Brood centers on the implosion of a family. And because it is a royal family whose domains span the English Channel and whose alliances encompass the Christian world, that collapse will have dire consequences. This is a story of betrayal as Henry's three eldest sons and his wife enter into a rebellion against him, aligning themselves with his bitterest enemy, King Louis of France. But it is also the story of a great king whose brilliance forged an empire but whose personal blind spots led him into the most serious mistake of his life.